Posterior Tibial Tendon Transfer for Central Foot Drop: A Case Report - Butarbutar, John; Phandu, Mirna; Siahaan, Lasa Dhakka; Suvarly, Prettysia (Open Access Macedonian Journal of Medical Sciences, 2022)
INTRODUCTION: Peripheral causes of foot drop are widely known. However, causes stemming from the central nervous system are rare. Posterior tibial tendon (PTT) transfer has been widely used for treating peripheral causes of foot drop but not central causes. We report a case of central foot drop (CFD) that was corrected with PTT transfer. CASE REPORT: A 68-year-old female presented with progressive weakness and numbness of both feet due to old compression fracture of the 12th thoracic spine. She also had Parkinson disease with gait rigidity. The patient was diagnosed with central foot drop. The left foot PTT transfer was done through the interosseous membrane and fixed to the navicular bone with an interference screw. Three months after the procedure, there is an improvement on the gait, and the foot drop is corrected. PTT transfer has a good outcome in peripheral foot drop. However, it is still questionable for the CFD case. In our case, PTT transfer was considered because it is less invasive, and tenodesis or ankle fusion still could be performed later if the PTT transfer outcome is not favorable. CONCLUSION: PTT transfer is a possible option to correct CFD. It is less invasive and has a good outcome.